Factors Affecting to Thai Students Decision Making to Join Work and Travel Program in USA - Tanatchat Maeluskul ธนัตถ์ฉัตร์ เมล์ลุสกุล (Dusit Thani College Journal, 2018)
This research aimed to study the main factors which effect to the decision making of Thai students on Work and Travel in USA program. This study used questionnaire to collect data from 400 students who join the program by contact with the agencies. The research shows that most of students are woman who are 20-30 years old, studying in Government’s University as year 2. They have their pocket money between 10,001-15,000 THB/month and it was their first time to join the program. The external factor to affect their decision making is society effect, they believe that Work and Travel Program might help them to develop their English skill. Moreover, the Marketing Mix, Place, of the agents also affect their decision the hypothesis in term of demography are not the main reason to affect decision making to join the program. By the way, the external factors and Marketing Mix of agents are the main reason to affect decision making to join Work and Travel program in USA.